2017
DOI: 10.1111/and.12883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ghrelin on total antioxidant capacity, lipid peroxidation, sperm parameters and fertility in mice against oxidative damage caused by cyclophosphamide

Abstract: Cyclophosphamide is a drug used for chemotherapy and as an immune-suppressive in the organ transplantation. Despite its many clinical implications in the treatment of cancers, this drug has toxic effects on the reproductive system. This study aimed to evaluate the effect of ghrelin against the damages caused by cyclophosphamide. In this experimental study, 40 male mice were randomly divided into four groups: (i) control; (ii) cyclophosphamide; (iii) cyclophosphamide + ghrelin; and (iv) ghrelin. Cyclophosphamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…In a rat model of varicocele, Asadi et al [45] demonstrated that ghrelin can decrease the oxidative stress (evaluated by means of MDA) caused by varicocele and enhance the activity of antioxidant enzymes. In addition, ghrelin attenuates the negative effects of cyclophosphamide, a chemotherapeutic and immune-suppressor drug, upon sperm parameters by reducing oxidative stress and LPO of sperm membranes and by enhancing the antioxidant activity [18]. These recent reports are extremely in accordance with our observations made in human semen.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a rat model of varicocele, Asadi et al [45] demonstrated that ghrelin can decrease the oxidative stress (evaluated by means of MDA) caused by varicocele and enhance the activity of antioxidant enzymes. In addition, ghrelin attenuates the negative effects of cyclophosphamide, a chemotherapeutic and immune-suppressor drug, upon sperm parameters by reducing oxidative stress and LPO of sperm membranes and by enhancing the antioxidant activity [18]. These recent reports are extremely in accordance with our observations made in human semen.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the reproductive system, a protective activity of ghrelin was observed in different researches, performed in animal models, demonstrating that this peptide can decrease the testicular damages [17, 4244]. Recent studies deal with the defensive role of ghrelin that can exert beneficial activity on redox imbalance for its anti-inflammatory and antioxidant properties also in the male reproductive system [18, 45–47]. In a rat model of varicocele, Asadi et al [45] demonstrated that ghrelin can decrease the oxidative stress (evaluated by means of MDA) caused by varicocele and enhance the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This role of ghrelin is presumably due to its antioxidative activity. In previous studies, it has been proved that the administration of ghrelin can prevent destructive effects of various factors such as chemotherapy (Salimnejad et al., ), cryptorchidism (Kheradmand et al., ) and cadmium toxicity (Kheradmand et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of ghrelin on different tissues under hypoxic conditions have recognised that it can significantly reduce the harmful effects induced by hypoxia and protect the tissue against damages caused by oxidative stress induced by hypoxia (Aliparasti, Alipour, Almasi, & Feizi, ; Bavil et al., ; Omrani, Alipour, & Mohaddes, ). Ghrelin does this process by reducing lipid peroxidation and also increasing total antioxidant capacity (Salimnejad et al., ). In the current study, ghrelin has likely prevented the effects of hypoxia on spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%